2014
DOI: 10.1371/journal.pone.0108051
|View full text |Cite
|
Sign up to set email alerts
|

RNA Expression Profiling of Human iPSC-Derived Cardiomyocytes in a Cardiac Hypertrophy Model

Abstract: Cardiac hypertrophy is an independent risk factor for cardiovascular disease and heart failure. There is increasing evidence that microRNAs (miRNAs) play an important role in the regulation of messenger RNA (mRNA) and the pathogenesis of various cardiovascular diseases. However, the ability to comprehensively study cardiac hypertrophy on a gene regulatory level is impacted by the limited availability of human cardiomyocytes. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) offer the oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 55 publications
5
60
0
1
Order By: Relevance
“…The miR‐590 family, more specifically, which is comprised of 2 miRNAs—miR‐590‐5p and miR‐590‐3p—is thought to play a key role in cardiovascular disease through its protection of blood vessels, regulation of lipid metabolism, and prevention of myocarditis and atherosclerosis through its target genes . miR‐590 is expressed in human induced pluripotent stem‐cell‐derived cardiomyocytes and in the human heart . miR‐590 regulates signaling pathways (TGF‐β, protein kinase B) involved in cardiac fibrosis/remodeling, embryonic stem cell proliferation/cardiac differentiation, and metabolism by suppressing TGF‐β receptor II .…”
Section: Discussionmentioning
confidence: 99%
“…The miR‐590 family, more specifically, which is comprised of 2 miRNAs—miR‐590‐5p and miR‐590‐3p—is thought to play a key role in cardiovascular disease through its protection of blood vessels, regulation of lipid metabolism, and prevention of myocarditis and atherosclerosis through its target genes . miR‐590 is expressed in human induced pluripotent stem‐cell‐derived cardiomyocytes and in the human heart . miR‐590 regulates signaling pathways (TGF‐β, protein kinase B) involved in cardiac fibrosis/remodeling, embryonic stem cell proliferation/cardiac differentiation, and metabolism by suppressing TGF‐β receptor II .…”
Section: Discussionmentioning
confidence: 99%
“…For example, iPSC-CMs are being used in cell-based assays to model susceptibility to drug-induced cardiotoxicity (75,76), thereby allowing researchers to predict adverse drug responses more accurately in patients with different genetic backgrounds. Similarly, iPSC-CMs have been used to understand the disease progression of diabetic cardiomyopathy (77), viral myocarditis (78), cardiac hypertrophy (79), and genetic polymorphism-induced cardiac ischemia (80). …”
Section: Applications Of Ipscsmentioning
confidence: 99%
“…In a separate study, microRNA (miRNA) sequencing showed that ET-1 treatment in hiPSC-CMs leads to differential expression of 250 known (e.g., miR-23a-3p and miR208a-3p) and 34 novel miRNAs, the majority of which were associated with corresponding mRNA expression changes (2). Some of the complex RNA regulatory mechanisms associated with cardiac hypertrophy were involved in cardiovascular development (e.g., MEF2C), cell proliferation and transformation (e.g., MYC, FOS, TGFB2, and TGFBR3), and mitogen-activated protein kinase signal transduction (e.g., MAP3K9 and MAP2K6).…”
Section: Secondary Cardiomyopathymentioning
confidence: 99%